Organic-inorganic composite shell phase change microcapsule and preparation method thereof

By using the composite shell layer of titanium dioxide and polyurethane, the organic-inorganic composite shell layer is transformed into microcapsules, which solves the problem of poor thermal and thermal stability of the phase transformation of the phase transformation in the existing technology, and realizes high heat conduction, The effects of thermal stability and high -inclusion rate have expanded its application field.

CN119327375AActive Publication Date: 2025-01-21EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411897572.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-21
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing phase-change microcapsules have problems of poor thermal conductivity and poor thermal stability in practical applications, which limits the widespread application of latent heat energy storage systems.

Method used

The composite shell material of titanium dioxide and polyurethane is used to modify the micro-capsule in the interface polymerizing organic-inorganic composite shell layer to improve its heat conduction and thermal stability.

Benefits of technology

The thermal conductivity and thermal stability of the microcapsule are significantly improved, the effect of high sealing rate and high thermal cycle stability is achieved, and the application range of phase -changing microcapsules is broaden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327375A_ABST
    Figure CN119327375A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: uniformly mixing a phase-change material and an oil-soluble monomer to obtain a dispersed phase, dissolving an emulsifier in deionized water to obtain a continuous phase, dropwise adding the dispersed phase into the continuous phase, and emulsifying to obtain an O / W emulsion; dissolving a water-soluble monomer in deionized water, slowly dropwise adding the water-soluble monomer solution into the O / W emulsion, controlling the mechanical stirring speed, temperature and time, carrying out interfacial polymerization reaction, and washing, filtering and drying the obtained product to obtain an organic shell layer pre-microcapsule; dispersing the pre-microcapsule into deionized water to obtain a pre-microcapsule suspension, adding a titanium source into the pre-microcapsule suspension, controlling the temperature for reaction, obtaining a product through hydrolysis liquid phase deposition, and washing, filtering and drying the product to obtain the organic-inorganic composite shell phase change microcapsule, so that the effects of high encapsulation efficiency and high thermal cycling stability are achieved, and the organic-inorganic composite shell phase change microcapsule is prepared. The encapsulation efficiency can reach 70.50%, and the phase change enthalpy value reaches up to 160J / g or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of latent heat energy storage, and in particular to an organic-inorganic composite shell phase change microcapsule and a preparation method thereof. Background Art

[0002] In order to improve the utilization efficiency of thermal energy, thermal energy storage technology has been widely developed, including sensible heat storage, latent heat storage and reversible thermochemical reactions. Among them, latent heat storage based on phase change materials (PCMs) is very attractive because of its high energy storage density, simple operation, and ability to solve the contradiction between energy supply and demand in time and space. Solid-liquid PCMs have outstanding advantages such as low density, large energy storage capacity, good chemical stability, and suitable phase change temperature, and are widely used. However, solid-liquid PCMs have problems of low thermal conductivity and easy leakage in practical applications, which limits the application of latent heat storage systems in various fields.

[0003] In order to solve the above bottlenecks, researchers have used various encapsulation methods to encapsulate these materials to construct shape-stable PCMs. The most popular method is to use microencapsulation technology to encapsulate PCMs in shell materials to form phase change microcapsules. These microcapsules can be made of various shell materials, including organic, inorganic and composite shell materials. However, it is worth noting that organic shell phase change microcapsules have high chemical stability and excellent corrosion resistance, but their thermal conductivity is generally poor, while phase change microcapsules with inorganic material shells are brittle and prone to leakage. Organic-inorganic composite shell phase change microcapsules can combine the advantages of organic shells and inorganic shells, improving the thermal conductivity of microcapsules while improving their chemical stability.

[0004] At present, melamine formaldehyde resin, urea formaldehyde resin and polymethyl methacrylate are the most reported and widely used microcapsule organic shell materials. However, the small molecules (such as formaldehyde, acrylate, etc.) remaining in the reaction process of the above resins will pose a serious threat to the environment and human health. In contrast, the preparation process of polyurethane does not produce harmful small molecules, and the prepared phase change microcapsules have good application prospects, especially the initial reaction rate of diisocyanate and polyol is relatively low. The mechanical properties of phase change microcapsules can be improved by adjusting the structure of polyurethane.

[0005] Titanium dioxide has the characteristics of low cost, non-toxicity, high thermal conductivity, high chemical stability and high thermal stability. It is also an excellent ultraviolet absorbing material, which can effectively improve the application value of phase change materials. It can not only assist in the shaping of phase change materials, but also solve the problem of poor thermal conductivity of phase change materials.

[0006] Therefore, the present invention provides a novel organic-inorganic composite shell phase change microcapsule and a preparation method thereof, a preparation process of a composite shell phase change microcapsule of titanium dioxide and polyurethane, which can effectively combine the advantages of an organic shell with the advantages of an inorganic shell, significantly improve the thermal conductivity and thermal stability of the microcapsule, and broaden the application scope of the phase change microcapsule, which is of great significance for promoting the green development of phase change material microcapsule technology. Summary of the invention

[0007] The purpose of the present invention is to provide an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, so as to solve the technical problems in the prior art that the organic shell of the phase change microcapsule has poor thermal conductivity and the inorganic shell has poor thermal stability. The prepared composite shell phase change microcapsule has good thermal stability, thermal conductivity and high encapsulation rate.

[0008] The purpose of the present invention is achieved through the following technical solutions: A method for preparing an organic-inorganic composite shell phase change microcapsule comprises the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a beaker, 4-4.2 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a centrifuge tube, 0.54-0.56 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise to the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification. The emulsification was performed for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly add the obtained triethanolamine aqueous solution dropwise into the water-in-oil emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven at 50-70°C for 12-20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: Pre-microcapsules were dispersed in 30 ml of deionized water in a beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the suspension was reacted at 35-65 °C for 4-6 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed with deionized water for 3-5 times, filtered, and dried in an oven at 50 °C for 22-26 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0009] The present application also provides an organic-inorganic composite shell phase-change microcapsule, which is prepared by the above-mentioned method for preparing the organic-inorganic composite shell phase-change microcapsule.

[0010] Due to the application of the above technical solution, the present invention has the following beneficial effects compared with the prior art: 1. The present invention prepares a novel organic-inorganic composite shell phase change microcapsule, the microcapsule has a smooth surface, uniform particle size, and good dispersibility; 2. The organic-inorganic composite shell phase-change microcapsules prepared by the present invention achieve the effects of high encapsulation rate and high thermal cycle stability. The encapsulation rate can reach 70.50%, and the phase change enthalpy value is as high as 160 J / g or more; 3. The organic-inorganic composite shell phase-change microcapsules prepared by the present invention are environmentally friendly. The process for preparing the phase-change microcapsules adopts the interfacial polymerization method, the reaction is easy to control, the process is simple, and it is easy to realize industrial production and application; 4. The organic-inorganic composite shell phase change microcapsules prepared by the present invention combine the advantages of the organic shell (flexibility and thermal stability) with the advantages of the inorganic shell (flame retardancy and thermal conductivity), broadening the scope of use of the phase change microcapsules. They can be applied to electronic equipment, textiles, energy-saving buildings, solar energy storage, industrial heat recovery, greenhouse agriculture, health care, aerospace and many other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, some of the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be made based on these drawings without paying any creative work.

[0012] Figure 1 This is a scanning electron microscope (SEM) image of the organic-inorganic composite shell phase change microcapsule of Example 1 of the present invention; Figure 2 This is a transmission electron microscope (TEM) picture of the organic-inorganic composite shell phase change microcapsule of Example 1 of the present invention. DETAILED DESCRIPTION

[0013] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, a specific implementation scheme is now described in detail.

[0014] The present invention is further described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to the different requirements of specific use, and the implementation conditions not indicated are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0015] Example 1 See attached Figure 1-2This embodiment provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.54 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0016] Comparative Example 1 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4.8 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.57 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0017] Comparative Example 2 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 1.6 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.47 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise to the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0018] Comparative Example 3 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.54 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 10,000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0019] Comparative Example 4 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.54 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise to the continuous phase at a homogenizing shear rate of 6000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0020] Comparative Example 5 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.54 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 50 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 45 ml of ammonium fluorotitanate solution and 135 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0021] Comparative Example 6 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.54 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification. The emulsification was performed for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 50 ml of ammonium fluorotitanate solution and 150 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0022] Comparative Example 7 This comparative example provides an organic-inorganic composite shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 1.1 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly drop the obtained triethanolamine aqueous solution into the O / W emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: The pre-microcapsules were dispersed in 30 ml of deionized water in a 200 ml beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the mixture was reacted at 50 ° C for 5 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed four times with deionized water, filtered, and dried in an oven at 50 ° C for 24 h to obtain the organic-inorganic composite shell phase change microcapsules.

[0023] Comparative Example 8 This comparative example provides an organic shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.54 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly add the obtained triethanolamine aqueous solution dropwise into the O / W emulsion. Stirring is continued for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization reaction. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. The obtained product is washed with anhydrous ethanol and deionized water, filtered, and dried for 12 h to obtain organic shell phase change microcapsules.

[0024] Comparative Example 9 This comparative example provides an organic shell phase change microcapsule and a preparation method thereof, comprising the following steps: (1) Preparation of oil-in-water (O / W) emulsion: At room temperature, in a 50 ml beaker, 4 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a 50 ml centrifuge tube, 0.57 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise into the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification for 5 min until a completely uniform and viscous O / W emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly add the obtained triethanolamine aqueous solution dropwise into the O / W emulsion. Stirring is continued for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization reaction. Place the centrifuge tube in an oven and polymerize at 70°C for 20 h. The obtained product is washed with anhydrous ethanol and deionized water, filtered, and dried for 12 h to obtain organic shell phase change microcapsules.

[0025] The phase change microcapsules obtained in the above examples and comparative examples were tested, and the test results are shown in Table 1.

[0026] Table 1

[0027] According to the above table and attached Figure 1 And attached Figure 2 It can be seen that the present invention: Example 1, Comparative Example 1, Comparative Example 2 Under the same other conditions, by adjusting the dosage ratio of the two reaction monomers, it can be clearly seen that when the dosage of triethanolamine is too high or too low, the encapsulation rate is significantly reduced; when the dosage ratio of triethanolamine to isophorone diisocyanate is 1:2.5, the encapsulation effect is the best; In Example 1, Comparative Example 3 and Comparative Example 4, under the same other conditions, by adjusting the emulsification shear rate, it can be clearly seen that the encapsulation effect is best when the emulsification shear rate is 8000 rpm; Example 1, Comparative Example 5, Comparative Example 6 Under other conditions that are the same, by adjusting the amount of ammonium fluorotitanate, it is found that as the amount of ammonium fluorotitanate increases, the encapsulation rate gradually decreases; Example 1 and Comparative Example 7: Under the same other conditions, by adjusting the amount of emulsifier, it can be clearly seen that the less the amount of emulsifier, the higher the encapsulation rate; Comparative Example 8 and Example 1; Comparative Example 9 and Comparative Example 1 Under other conditions that are the same, Comparative Examples 8 and 9 are not loaded with an inorganic shell layer, and the encapsulation rate of Comparative Example 8 is significantly lower than that of Example 1, and the encapsulation rate of Comparative Example 9 is significantly lower than that of Comparative Example 1; the encapsulation rates of Comparative Examples 8 and 9 are reduced by about 1.5% after fifty heating and cooling cycles, and the encapsulation rates of Example 1 and Comparative Example 1 are only reduced by about 0.8% after fifty heating and cooling cycles, indicating that the thermal cycle stability of Example 1 and Comparative Example 1 is significantly improved; The encapsulation rate of Example 1 is as high as 70.50%, and it has the advantages of both the organic shell layer and the inorganic shell layer, which significantly improves the mechanical properties and thermal conductivity of the material.

[0028] In summary, the novel organic-inorganic composite shell phase change microcapsules prepared by the present invention have a smooth surface, uniform particle size and good dispersibility; the organic-inorganic composite shell phase change microcapsules prepared by the present invention achieve the effects of high encapsulation rate and high thermal cycle stability, the encapsulation rate can reach 70.50%, and the phase change enthalpy value is as high as 160 J / g or more; the organic-inorganic composite shell phase change microcapsules prepared by the present invention are environmentally friendly, and the process for preparing the phase change microcapsules adopts the interfacial polymerization method, the reaction is easy to control, the process is simple, and it is easy to realize industrial production and application; the organic-inorganic composite shell phase change microcapsules prepared by the present invention combine the advantages of the organic shell (flexibility and thermal stability) with the advantages of the inorganic shell (flame retardancy and thermal conductivity), broaden the scope of use of the phase change microcapsules, and can be applied to electronic equipment, textiles, energy-saving buildings, solar energy storage, industrial heat recovery, greenhouse agriculture, health care, aerospace and many other fields.

[0029] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an organic-inorganic composite shell phase change microcapsule, characterized in that: The following steps are involved: (1) Preparation of water-in-oil emulsion: At room temperature, in a beaker, 4-4.2 g of isophorone diisocyanate was dissolved in 15 g of n-hexadecane to obtain a dispersed phase. In a centrifuge tube, 0.54-0.56 g of the emulsifier sodium dodecylbenzene sulfonate was dissolved in 4 g of deionized water to obtain a continuous phase. The dispersed phase was added dropwise to the continuous phase at a homogenizing shear rate of 8000 rpm for emulsification. The emulsification was performed for 5 min until a completely uniform and viscous water-in-oil emulsion was formed. (2) Synthesis of organic shell pre-microcapsules: Weigh 1.6 g of triethanolamine and dissolve it in an equal amount of deionized water. Slowly add the obtained triethanolamine aqueous solution dropwise into the water-in-oil emulsion. Stir for 30 min at 60°C and 600 rpm for mechanical stirring to cause interfacial polymerization. Place the centrifuge tube in an oven at 50-70°C for 12-20 h. Wash the obtained product with anhydrous ethanol and deionized water, filter, and dry for 12 h to obtain white powdery organic shell pre-microcapsules. (3) Preparation of organic-inorganic composite shell phase change microcapsules: Pre-microcapsules were dispersed in 30 ml of deionized water in a beaker to obtain a pre-microcapsule suspension, to which 40 ml of ammonium fluorotitanate solution and 100 ml of boric acid solution were added, and the suspension was reacted at 35-65 °C for 4-6 h. A primary product was obtained through hydrolysis reaction and precipitation. The primary product was washed with deionized water for 3-5 times, filtered, and dried in an oven at 50 °C for 22-26 h to obtain the organic-inorganic composite shell phase change microcapsules.

2. An organic-inorganic composite shell phase change microcapsule, characterized in that: The microcapsules are prepared by the method for preparing organic-inorganic composite shell phase change microcapsules as claimed in claim 1.

Citation Information

Patent Citations

  • Double-chamber microcapsule with self-repairing function, and preparation method thereof

    CN111558348A

  • Phase change microcapsule having high blending fluidity and high phase change latent heat and preparation method therefor

    WO2021012302A1